Nigeria : Third Review Under the Policy Support Instrument; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Nigeria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper examines Nigeria's Third Review Under the Policy Support Instrument. Robust growth, lower inflation, a dramatic decline in debt, and an accumulation of significant reserves are among the notable economic achievements. It will be important to consolidate and institutionalize these gains as the foundations for sustained and improved economic performance. Non-oil growth accelerated and its prospects are promising. Inflation remained in line with the single-digit program target owing to a likely increase in confidence and money demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet